2016
DOI: 10.1021/acs.energyfuels.6b01857
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Chemistry for Butanol Isomers at Engine-Relevant Conditions

Abstract: Butanol has received significant research attention as the second-generation biofuel in the past few years. In the present study, skeletal mechanisms for four butanol isomers were generated from two widely accepted, well-validated detailed chemical kinetic models for the butanol isomers. The detailed models were reduced using a two-stage approach consisting of the directed relation graph with error propagation and sensitivity analysis. During the reduction process, issues encountered with pressure-dependent re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Recently, basic research into new catalysts for the synthesis of higher alcohols on a renewable basis via aldolic condensation has been gaining increasing attention [1][2][3][4][5][6]. Amongst these alcohols, iso-butanol in particular has been identified as very promising from various perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, basic research into new catalysts for the synthesis of higher alcohols on a renewable basis via aldolic condensation has been gaining increasing attention [1][2][3][4][5][6]. Amongst these alcohols, iso-butanol in particular has been identified as very promising from various perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction rates from these calculations can be compared to estimates from the detailed isobutanol mechanism by Sarathy et al 15 Two other isobutanol mechanisms, published by Hui et al 7 and Merchant et al, 11 do not include explicit representation of peroxy radicals, so these cannot be compared directly to the calculations here.…”
Section: Comparison With a Detailed Combustion Mechanismmentioning
confidence: 99%
“…Detailed isobutanol mechanisms typically deviate more from experiments than do models of n-butanol, tert-butanol, and sec-butanol. 7,8 Multiple inter-model comparisons using detailed isobutanol models have showed that at lean, low-temperature conditions the models yield a wide range of ignition timings that deviate from experimental ignition delay measurements in homogeneous charge compression 9 and shock tube setups. 10 One mechanism shows the largest deviations from experiments below 850 K and at fuel lean conditions, indicating that the dependence on O 2 might be incorrectly described.…”
Section: Introductionmentioning
confidence: 99%
“…I-butanol is a versatile base chemical and has also been tested as a carbon-neutral fuel [25]. Thanks to its higher octane numbers, lower soot production, and higher compressibility in internal combustion engines, it has emerged as a superior fuel over n-butanol [26][27][28].…”
Section: Introductionmentioning
confidence: 99%